AB0650 LATENT TUBERCULOSIS SCREENING AND MANAGEMENT BEFORE BIOLOGIC AGENTS INSTAURATION AND RISK OF REACTIVATION: THE EXPERIENCE OF AN ENDEMIC TUBERCULOSIS COUNTRY. (23rd January 2014) - Mahmoud, I.; Dridi, L.; Saidane, O.; Sahli, H.; Tekaya, R.; Abdelmoula, L.; Chaabouni, L.; Zouari, R.
Abstract : Background: Using biologic agents has significantly improved the management of chronic inflammatory rheumatism. However, there is clear evidence that these treatments increase the risk of infections and tuberculosis reactivating (TB). Objectives: To specify latent TB screening procedures in Tunisian patients candidates for biologic agents and to assess the risk of subsequent reactivation. Methods: It's a retrospective monocentric study of medical records of patients with chronic inflammatory rheumatism receiving biologic agents (TNF alpha blockers and Rituximab) between 2007 and 2012 since at least 3 months. Before treatment instauration, latent TB infection was detected on the basis of history taking, physical examination, 5-unit intradermal tuberculin test (ITT), Chest X-ray and BK research in sputum and urine. In Tunisia all patients were vaccinated with Bacille Calmette-Guérin at birth and at the age of 6 years if schooled. The national Tunisian guidelines for TB management, in patients receiving biologic agents, were followed. The particularity of Tunisian recommendations is, before 2010, positive ITT was considered positive beyond 10mm, now the Affsaps recommendations are used. Patients outcome has been reported. Results: Eighty-three patients were included in this study with a mean age of 47 years. It was about 53 women and 30 men with rheumatoid arthritis (n=53), spondylarthropathis (n=28), refractory adult onset Still disease (n=1) and severe ocular involvement of Behçet disease (n=1). Ninety one prescriptions of biologic agents were reported. Etanercept was prescribed in 32 cases, infliximab in 26 cases, adalimumab in 10 cases and rituximab in 21 cases. History of TB was found in 2 patients. Physical examination was normal in all cases. The chest-X-ray showed suggestive images of TB in 1 patient proved to be sequellar in the lung scan. The ITT was< 5mm in 66 cases, between 5 and 10mm in 10 cases and >10mm in 7 cases. Prophylactic TB treatment by Izoniazide 5mk/kg/day and Rifampicine 10 mg/kg/day for 3 months was prescribed in 10 cases. It was indicated for positive ITT (8cases), opacity of the chest radiography (1case) and positive culture of mycobacterium TB in urine in 1case (in this case no urogenital TB was confirmed). Nine patients, seen before 2010, had ITT between 5 and 10mm and didn't receive chimioprophylaxis. The biotherapy was initiated 3 weeks after chemoprophylaxis beginning. During the following-up, 2cases of active pulmonary TB after the initiation of biologics was reported. The first case was in 48-years-old woman treated with rituximab, 26 months after the last infusion. Rituximab reintroduction, 2 months after TB treatment, was safe. The other case was a 28-years-old man treated with etanercept for 5months. In this tow cases, initially latent TB screening was negative. No case of TB reactivation has been reported after a mean follow-up of 16 months, even in the group of patients with ITT between 5 and 10mm who didn't receive preventive treatment. Conclusions: Our study showed that the Tunisian recommendations have prevented the occurrence of TB reactivation under biologic agents. The use of these treatments in an endemic country does not increase the risk of TB reactivation if preventive measures have been complied. Disclosure of Interest: None Declared